Pressed Juice Percentage Can Accurately Sort Beef into Categories of Predicted Juiciness - K. V. McKillip; A. K. Wilfong; J. M. Gonzalez; T. A. Houser; E. A. Boyle; J. A. Unruh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2016)
There are three main factors that contribute to meat palatability: tenderness, juiciness, and flavor (Bratzler, 1971). These three individual factors all play a role in the overall palatability perceived by a consumer. If a product fails for juiciness, there is a greater chance that it will fail in overall acceptability (Emerson et. al, 2013). In the past, research has established a method of segregating steaks based on tenderness acceptability. Researchers have been able to institute thresholds to be able to accurately explain at what shear force a steak will be rated tender by consumers. Similar methods have not been evaluated for juiciness until very recently when Woolley (2014) developed a method to objectively quantify beef juiciness. The method that was created included calculating the percentage of moisture loss from each sample after being compressed. From this work, thresholds for juiciness acceptability were established using loigistic regression; however, additional research is needed to verify these established thresholds. Therefore, the objective of this study was to determine the accuracy of previously established threshold values by testing consumer juiciness ratings for beef steaks in relation to objective juiciness measures.
Keywords: pressed juice percentage; juiciness; grade